Custard Apple Seed Oil Anti-Fly Property: A Review (International Journal of Innovative Research in Computer Science & Technology, 2022)
The house fly, Musca domestica L, has  been identified as a vector for a variety of human and  animal illnesses. Eradication of such pests needs the help  of insecticides which in turn has led to the growth in  insecticides or insect repellents which are not only  effective but are also non-toxic. In this paper, the anti-fly  property of custard apple (Annona muricata) seeds has  been shown against Musca domestica L. Firstly, oil was  extracted from the custard apple seeds. Afterwards, sugar  cubes were left untreated or coated with a fresh coat of  custard apple seed oil. After 120 hours, the freshly treated  sugar samples exhibited anti-fly property against the flies in this study. Moreover, spraying of a solution of custard  apple seed oil and water led to death of many flies. It can  thus be concluded that custard apple seed oil is a promising  natural anti-fly agent and the abundance of custard apple  seeds means that at an industrial scale such insecticide or  insect repellent can be produced.
Keywords: Custard apple seeds; Cyto-toxicity; House fly; Insect repellents; insecticide; Musca domestica L; MTT assay; sugar cubes